THE IMPORTANCE OF SOME SYNTHETIC DRUGS AND HORSERADISH IN THE TREATMENT OF ATHEROSCLEROSIS (Scientific journal of the Fergana State University, 2023)
Atherosclerosis is a chronic disease that occurs as a result of lipid and protein metabolism disorders, and is caused by deposition of certain fractions of cholesterol and lipoproteins in the vessels. The article provides information about some synthetic drugs used in the treatment of atherosclerosis and the importance of horseradish.